Autism Support Teachers’ Attitudes about Inclusion for Children with Autism - Rosen, Perri; Rotheram-Fuller, Erin; Mandell, David (Journal of the American Academy of Special Education Professionals, 2018)
This study examined autism support teachers’ attitudes about inclusion, as well as perceived barriers and resource needs. A survey was developed for this study and administered to 27 elementary teachers in autism support (AS) classrooms in a large, urban district. Approximately 75% of students in the sample were educated primarily in self-contained settings, although 70% had teachers who recommended more inclusion. AS teachers were more concerned about the readiness of general education teachers and their classrooms than the readiness of their students. The greatest needs were school-wide training (47%), acceptance of students with autism (38%), smaller class sizes (31%) and more support staff (31%). AS teachers’ attitudes about student placement were somewhat conflicted, underscoring the need to build school-wide capacity and promote greater acceptance.